NMR dispersion investigations of enzymatically degraded bovine articular cartilage. Issue 5 (13th May 2014) - Rössler, Erik; Mattea, Carlos; Stapf, Siegfried
Abstract : Purpose: Cross‐relaxation of protons with 14 N nuclei in proteins enhances relaxivity in the quadrupolar dip range of typically 2–3 MHz Larmor frequency. The magnitude of these dips was suggested as a means of assessing the degeneracy of articular cartilage during osteoarthritis (OA). However, so far only proteoglycans have been considered whereas collagen nitrogen was neglected. This study addresses the relative importance of glycosaminoglycans (GAG), collagen, and water content for the cross‐relaxation effect. Methods: Relaxation dispersion data were acquired for protons in samples of bovine articular cartilage, collagen, and GAG before and after the addition of trypsin or collagenase, and were compared with spatially resolved dGEMRIC experiments at 0.27 Tesla. Results: Both collagen as well as GAG show quadrupolar dips that strongly depend on hydration. For typical water concentrations in cartilage, the effect of enzymatic activity onto GAG is minor but a strong dependence on water concentration is found. Conclusion: Quadrupolar dips in the 1 H relaxation dispersion of cartilage possess similar contributions from both GAG and collagen. The reduction of the cross‐relaxation contribution observed in OA tissue is thus not directly proportional to GAG concentration, but maintains a collagen contribution and reflects predominantly the increase in water concentration during OA. Magn Reson Med 73:2005–2014, 2015. © 2014 Wiley Periodicals, Inc.